2019
DOI: 10.9734/ijtdh/2019/v35i130109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia after Initiation of Antiretroviral Therapy among HIV-infected Patients Attending University of Calabar Teaching Hospital Calabar, Nigeria

Abstract: Aims: To investigating some demographic variables and red cell parameters of infected persons already accessing antiretroviral therapy with a view to identifying sub- groups with higher proportions of anaemia.  Study Design:  Cross-sectional study. Place and Duration of Study: University of Calabar Teaching Hospital Calabar Nigeria, between August 2017 and July 2018. Methodology: Subjects comprised 60 male and female HIV-infected adults attending University of Calabar Teaching Hospital Calaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This present study revealed correlation between different stages of CD4 count and erythropoietin (EPO) among the study population. In supporting the findings in this study, Okafor reported that HIV has direct effect on the bone marrow through the expression of proinflammatory cytokines that suppress erythropoiesis (Okafor et al, 2019). Anaemia in HIV patients is caused by depressed bone marrow function by HIV infection leading to low production of erythropoietin which resulted into ineffective production of red blood cell (Esan et al, 2020), CD4>500 has higher mean value of EPO compared to CD4 200-499 and CD4<200 in HIV subjects on ART and ART-naïve confirming that the more the severity of HIV infection the lower the erythropoiesis.…”
Section: Discussionsupporting
confidence: 87%
“…This present study revealed correlation between different stages of CD4 count and erythropoietin (EPO) among the study population. In supporting the findings in this study, Okafor reported that HIV has direct effect on the bone marrow through the expression of proinflammatory cytokines that suppress erythropoiesis (Okafor et al, 2019). Anaemia in HIV patients is caused by depressed bone marrow function by HIV infection leading to low production of erythropoietin which resulted into ineffective production of red blood cell (Esan et al, 2020), CD4>500 has higher mean value of EPO compared to CD4 200-499 and CD4<200 in HIV subjects on ART and ART-naïve confirming that the more the severity of HIV infection the lower the erythropoiesis.…”
Section: Discussionsupporting
confidence: 87%
“…The lower Hb level in PLWHIV implies anemia and the possible reasons include poor utilization of iron, ineffective erythropoiesis and possible red cell destruction as reported in previous studies. [17,18] Neutropenia is the most common leucopenia occurring in HIV infected individuals. HIV infection on its own suppresses the bone marrow and leads to decreased levels of granulocyte colony-stimulating factor, and also affects the granulocyte-macrophage lineage, thus resulting in leukopenia and neutropenia.…”
Section: Discussionmentioning
confidence: 99%